Morphological changes in the kidneys of rats with experimental hemorrhagic stroke (intracerebral hemorrhage) - A. I. Gozhenko; V. N. Bibikova (Kazimierz Wielki University, 2018)
The article presents the results of the study of morphological changes in the kidneys in Wistar rats during the stroke. Hemorrhagic stroke modeling was performed by injecting 0.1-0.2 ml of autoblood through an opening in the temporal bone into the region of the inner capsule of the right hemisphere. To form a hematoma, a stereotaxic destruction was performed. The experimental group consisted of 6 animals, the control group was represented by intact rats (n=3) and rats after trepanation of the temporal bone but without the introduction of autoblood (n=3). The animals were removed from the experiment on days 3 and21. Inthe course of the study, the structural changes in the right and left kidneys were compared to determine the difference in the location of the disorders. According to the results of the histological examination of the medulla, the tendency to reduction of cytological disorders of the epithelium of the tubules of the left kidney was revealed, while in the right kidney the structural disturbances of the tubules of the nephrons and the collecting ducts of the papilla of the kidney were recorded. Based on these data, it is possible to assume renal involvement in rats on day 3 after a stroke and a frequency recovery on day 21. The described histological studies give  a new data on the development of structural changes in renal medulla in rats with hemorrhagic stroke, which can be associated with a violation of electrolyte exchanges at the level of the distal nephron segment.